Retrieval of total ozone column using high spatial resolution top-of-atmosphere measurements by OLCI/S-3 in the ozone Chappuis absorption band over bright underlying surfaces. (December 2021) - Kokhanovsky, Alexander; Iodice, Filippo; Lelli, Luca; Zschaege, Achim; De Quattro, Nicola; Gasbarra, Daniele; Retscher, Christian
Abstract: In this work we have developed a novel algorithm for the determination of the total ozone column (TOC) from spectral top-of-atmosphere solar backscattered light measurements in the spectral range 400-1020nm performed by the ESA Ocean and Land Colour Instrument on board Sentinel -3A, B. The algorithm can be applied for scenes over bright underlying surfaces including clouds, snow and ice (e.g., over Antarctica), where the ozone absorption feature in the Chappuis absorption band is clearly seen in registered top-of-atmosphere backscattered light spectra . The technique provides the possibility to perform the total ozone measurements on the spatial scale 300m, which can not be reached by other modern spaceborne measurements, aimed at total ozone observations such as TROPOMI, OMI, GOME-2, OMPS and other.